Examining the internalizing pathway to substance use frequency in 10 cultural groups - W. Andrew Rothenberg (2020)
© 2019 Elsevier Ltd Use of alcohol, tobacco, and drugs (i.e., substance use) is a leading cause of global health burden for 10-to-24-year-olds, according to the World Health Organization's index of number of years of life lost, leading international health organizations to prioritize the prevention of substance use before it escalates in adolescence. Pathways defined by childhood externalizing symptoms and internalizing symptoms identify precursors to frequent substance use toward which interventions can be directed. However, these pathways are rarely examined beyond the United States and Europe. We investigated these pathways in our sample of 1083 children from 10 cultural groups followed from ages 8–14. We found that age-10 externalizing symptoms predicted more frequent mother-reported age-13 and self-reported age-14 substance use. We also found that a depressive pathway, marked by behavioral inhibition at age 8 and subsequent elevation in depressive symptoms across ages 8–12 predicted more frequent substance use at age 13 and 14. Additionally, we found a combined externalizing and internalizing pathway, wherein elevated age-9 depressive symptoms predicted elevated externalizing symptoms at age-10 which predicted greater peer support for use at age-12, which led to more frequent substance use at age-13 and -14. These pathways remained significant within the cultural groups we studied, even after controlling for differences in substance use frequency across groups. Additionally, cultures with greater opportunities for substance use at age-12 had more frequent adolescent substance use at age-13. These findings highlight the importance of disaggregating between- and within-culture effects in identifying the etiology of early adolescent substance use.